Indigenous research ethics : claiming research sovereignty beyond deficit and the colonial legacy - George, Lily; Taori, Juan; MacDonald, Lindsey Te Ata o Tu (Advances in research ethics and integrity, 2020)
Given the extreme variety of research issues under investigation today and the multi-million-dollar industry surrounding research, it becomes extremely important that we ensure that research involving Indigenous peoples is ethically as well as methodologically relevant, according to the needs and desires of Indigenous peoples themselves. This distinctive volume presents Indigenous research as strong and self-determined with theories, ethics and methodologies arising from within unique cultural contexts. Yet the volume makes clear that challenges remain, such as working in mainstream institutions that may not regard the work of Indigenous researchers as legitimate 'science'. In addition, it explores a twenty-first-century challenge for Indigenous people researching with their own people, namely the ethical questions that must be addressed when dealing with Indigenous organisations and tribal corporations that have fought for - and won - power and money. The volume also analyses Indigenous/non-Indigenous research partnerships, outlining how they developed respectful and reciprocal relationships of benefit for all, and argues that these kinds of best practice research guidelines are of value to all research communities.